An experimental investigation of vortex-induced vibration of a curved flexible pipe in shear flows - Zhu, Hongjun; Lin, Pengzhi; Yao, Jie (Ocean engineering, 2016)
Vortex-induced vibration (VIV) of a curved flexible pipe in shear flows was studied experimentally in the concave configuration. The curved pipe was fully immersed into the water with the aspect ratio of 108 and mass-damping ratio of 0.11. The high speed imaging technology was employed to record the pipe's vibration displacements in both in-line and cross-flow directions subject to the shear flows with 15 different velocities. Both amplitude and frequency are presented versus the reduced velocity for a Reynolds number ranging from 165 and 1129. The results reveal that different vibration frequencies exist at different positions of the pipe with the presentation of multi-mode-response, and the excited modes vary with the incoming speed. The highest mode in the in-line direction is the third mode, while it is the second mode in the cross-flow direction. Eight-shape trajectories are presented in the middle part of the pipe, while the trajectories evolve to half-moon format at the two ends of pipe. Flow visualizations show that 2P or P+S wake pattern presents at the locations corresponding to the two peaks of the second-order response, while 2S pattern mainly appears at the position corresponding to the trough. The wake mainly presents a P+S mode at the location corresponding to the peak of the first-order response, while 2S mode is the main pattern in other locations. •The overall response of a curved pipe under log-law shear flows is studied.•The non-intrusive technique of high speed imaging method is employed.•Fifteen shear flow profiles with Re ranges from 165 to 1129 are considered.•Multi-mode-response presents with different frequencies existing at different positions.•The trajectories along the length of the pipe indicate key vibration characteristics.